1994
DOI: 10.1152/jn.1994.71.6.2074
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical entrainment of fictive locomotion in the decerebrate cat

Abstract: 1. We examined the ability of muscular and joint afferents from the hip region to entrain fictive locomotion evoked by stimulation of the mesencephalic locomotor region in the decerebrate cat by mechanically imposed, sinusoidal hip flexion and extension movements. 2. A method is presented for qualitative and quantitative analysis of entrainment. 3. Hip joint capsular afferents were shown by denervation experiments to be unnecessary for mediating locomotor entrainment. 4. As the population of muscular afferents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(138 citation statements)
references
References 24 publications
5
132
1
Order By: Relevance
“…Such an organization was suggested to explain the independence between changes in burst duration and cycle timing during paw shake (Koshland and Smith, 1989;Stein and Smith 1997). A similar separation of CPG function was suggested to explain how sensory stimulation could alter locomotor cycle timing without altering the level of motoneuron activity (Kriellaars et al, 1994). In the latter scheme the CPG was divided into a half-center rhythm generator and "reciprocity modules" each of which was responsible for the depolarization and hyperpolarization of subsets of motoneurons (Jordan, 1991).…”
Section: Two-level Half-center Cpg Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Such an organization was suggested to explain the independence between changes in burst duration and cycle timing during paw shake (Koshland and Smith, 1989;Stein and Smith 1997). A similar separation of CPG function was suggested to explain how sensory stimulation could alter locomotor cycle timing without altering the level of motoneuron activity (Kriellaars et al, 1994). In the latter scheme the CPG was divided into a half-center rhythm generator and "reciprocity modules" each of which was responsible for the depolarization and hyperpolarization of subsets of motoneurons (Jordan, 1991).…”
Section: Two-level Half-center Cpg Modelsmentioning
confidence: 96%
“…Finally, a regulatory scheme affecting synaptic transmission would have difficulty accounting for the independent control of rhythm and motoneuron recruitment. The rhythm can be slowed or accelerated by sensory stimulation without altering the level of motoneuron activity (e.g., Kriellaars et al, 1994) and motoneuron activation can be altered without affecting cycle timing Guertin et al, 1995;Stecina et al, 2005) As discussed below, a two-level CPG can explain both the sensory control of locomotion and the occurrence of resetting and nonresetting deletions. …”
mentioning
confidence: 99%
“…Little is known of the mechanisms of speed control in mammals (Kriellaars et al, 1994;Orlovsky and Shik, 1976). Recently, however, studies in newborn mice revealed that the cycle period of locomotor output lengthened when neurones of V1 lineage were silenced (Fig.…”
Section: Regulation Of Locomotor Speed: V1 and Hb9 Interneuronesmentioning
confidence: 99%
“…This perturbation occurred just before the swing-to-stance transition. This appears to be a period when the system is particularly sensitive to information related to afferent input such as hip position (Grillner and Rossignol, 1978;Kriellaars et al, 1994). In young infants (Pang and Yang, 2002) a perturbation applied during the stance phase has the greatest influence on the subsequent step cycle when the perturburbation is timed to occur near the stance-to-swing transition.…”
Section: Larger Responses To Late Swing and To Hip Perturbationsmentioning
confidence: 99%